In-cage sandbox as a ground substitute for farmed blue foxes (Alopex lagopus) : effects on digging and welfare - Korhonen, Hannu T; Jauhiainen, Lauri; Rekilä, Teppo (Agricultural Institute of Canada, 2003)
V 2004 ok